Regulatory and Clinical Experiences with Biosimilar Filgrastim in the U.S., the European Union, Japan, and Canada. (6th March 2019) - Chen, Brian; Nagai, Sumimasa; Armitage, James O.; Witherspoon, Bartlett; Nabhan, Chadi; Godwin, Ashley C.; Yang, Y. Tony; Kommalapati, Anuhya; Tella, Sri Harsha; DeAngelis, Carlo; Raisch, Dennis W.; Sartor, Oliver; et al.
Abstract: : Biosimilar filgrastims are primarily indicated for chemotherapy‐induced neutropenia prevention. They are less expensive formulations of branded filgrastim, and biosimilar filgrastim was the first biosimilar oncology drug administered in European Union (EU) countries, Japan, and the U.S. Fourteen biosimilar filgrastims have been marketed in EU countries, Japan, the U.S., and Canada since 2008, 2012, 2015, and 2016, respectively. We reviewed experiences and policies for biosimilar filgrastim markets in EU countries and Japan, where uptake has been rapid, and in the U.S. and Canada, where experience is rapidly emerging. U.S. regulations for designating biosimilar interchangeability are under development, and such regulations have not been developed in most other countries. Pharmaceutical substitution is allowed for new filgrastim starts in some EU countries and in Canada, but not Japan and the U.S. In EU countries, biosimilar adoption is facilitated with favorable hospital tender offers. U.S. adoption is reportedly 24%, while the second filgrastim biosimilar is priced 30% lower than branded filgrastim and 20% lower than the first biosimilar filgrastim approved by the U.S. Food and Drug Administration. Utilization is about 60% in EU countries, where biosimilar filgrastim is marketed at a 30%–40% discount. In Japan, biosimilar filgrastim utilization is 45%, primarily because of 35% discounts negotiated by Central Insurance and hospital‐only markets. Overall, biosimilar filgrastim adoption barriers are small in many EU countries and Japan and are diminishing in Canada in the U.S. Policies facilitating improved U.S. adoption of biosimilar filgrastim, based on positive experiences in EU countries and Japan, including favorable insurance coverage; larger price discount relative to reference filgrastim pricing; closing of the "rebate trap" with transparent pricing information; formal educational efforts of patients, physicians, caregivers, and providers; and allowance of pharmaceutical substitution of biosimilar versus reference filgrastim, should be considered. Implications for Practice: We reviewed experiences and policies for biosimilar filgrastims in Europe, Japan, Canada, and the U.S. Postmarketing harmonization of regulatory policies for biosimilar filgrastims has not occurred. Acceptance of biosimilar filgrastims for branded filgrastim, increasing in the U.S. and in Canada, is commonplace in Japan and Europe. In the U.S., some factors, accepted in Europe or Japan, could improve uptake, including acceptance of biosimilars as safe and effective; larger cost savings, decreasing "rebate traps" where pharmaceutical benefit managers support branded filgrastim, decreased use of patent litigation/challenges, and allowing pharmacists to routinely substitute biosimilar for branded filgrastim. Abstract : Filgrastim patents have expired worldwide, opening the way for biosimilars. Biosimilar filgrastim, a less expensive formulation of reference filgrastim, is the most common biosimilar oncology drug administered worldwide and is hoped to decrease oncology pharmaceutical costs in the U.S., as has happened in other countries. This article reviews the experiences and policies related to biosimilar filgrastim markets in European countries and Japan, where uptake has been rapid, and in the U.S. and Canada, where experience is emerging.